John Wickham's new surgery: 'minimally invasive therapy", innovation, and approaches to medical practice in twentieth-century Britain - Kneebone,RL; Frampton,S (Social History of Medicine, 2016)
The term ‘minimally invasive’ was coined in 1986 to describe a range of procedures that involvedmaking very small incisions or no incision at all for diseases traditionally treated by open surgery.We examine this major shift in British medical practice as a means of probing the nature of surgical innovationin the twentieth century. We first consider how concerns regarding surgical invasiveness hadlong been present in surgery, before examining how changing notions of post-operative care formed afoundation for change. We then go on to focus on a professional network involved in the promotionof minimally invasive therapy led by the urologist John Wickham. The minimally invasive movement,we contend, brought into focus tensions between surgical innovation and the evidence-based modelof medical practice. Premised upon professional collaborations beyond surgery and a re-positioning ofthe patient role, we show how the movement elucidated changing notions of surgical authority.